Pregnancy-induced thrombotic thrombocytopoenic purpura (TTP) complicated by atypical posterior reversible encephalopathy syndrome (PRES) and acute pancreatitis - Rithik Naik Korra; Nikhil Kumar Balagoni (Clinical Medicine)
Introduction: Thrombotic thrombocytopoenic purpura (TTP) is a life-threatening thrombotic microangiopathy characterised by thrombocytopenia, microangiopathic haemolytic anaemia, neurological dysfunction and renal impairment. It arises from a severe deficiency in ADAMTS13, a von Willebrand factor-cleaving protease, leading to uncontrolled platelet aggregation and widespread microvascular thrombosis. Pregnancy is a known trigger for TTP because of increased von Willebrand factor levels and decreased ADAMTS13 activity.1 Distinguishing TTP from other pregnancy-related thrombotic microangiopathies, such as Haemolysis, Elevated Liver Enzymes, Low Platelets (HELLP) syndrome and preeclampsia, is crucial for timely intervention.2 We present a case of a pregnant woman diagnosed with TTP complicated by posterior reversible encephalopathy syndrome (PRES), acute kidney injury (AKI) and acute pancreatitis. Materials and Methods: A 28-year-old gravida 2, para 1 woman presented with seizures, vomiting, fever, decreased fetal movement and visual impairment. Laboratory tests revealed thrombocytopenia (49,000/µL), anaemia (haemoglobin 13.5 g/dL), leucocytosis (white cell count 25,000/µL), and AKI (serum creatinine 2.49 mg/dL). Ultrasound confirmed intrauterine fetal demise. Neurological symptoms prompted a brain CT, which showed findings consistent with PRES. On Day 4, the patient developed epigastric pain, and laboratory tests revealed elevated amylase (770 U/L) and lipase (1930 U/L), confirming acute pancreatitis. A kidney biopsy on Day 15 demonstrated diffuse cortical necrosis with thrombotic microangiopathy. ADAMTS13 autoantibody levels were significantly elevated (48.0 AU/mL), confirming the diagnosis of TTP. The patient underwent plasma exchange therapy, haemodialysis and corticosteroid treatment. Results and Discussion: The patient's neurological symptoms improved with plasma exchange therapy, and visual acuity gradually returned. AKI required prolonged haemodialysis, but renal function showed partial recovery by discharge. Pregnancy-related TTP poses diagnostic challenges, with nearly 50% of cases occurring postpartum and associated with severe maternal and fetal complications.3 PRES, a rare complication of TTP, is often linked to hypertensive disorders, yet our patient was normotensive.4 Studies suggest that endothelial dysfunction and systemic inflammation contribute to PRES in normotensive patients. Acute pancreatitis in TTP is rare and may either result from or trigger microvascular thrombosis.5 Timely plasma exchange therapy is critical, because delayed treatment increases mortality risk. Unlike preeclampsia or HELLP syndrome, which resolve after delivery, TTP requires ongoing plasma exchange and immunosuppressive therapy.6 Emerging therapies, such as caplacizumab, show promise in refractory TTP, but its use in pregnancy remains experimental.7 Conclusion: This case highlights the importance of early recognition and differentiation of TTP from other pregnancy-related thrombotic microangiopathies. The coexistence of PRES and acute pancreatitis complicates the clinical course, requiring a multidisciplinary approach. Plasma exchange therapy remains the cornerstone of treatment, significantly improving maternal outcomes. Future research should explore optimised treatment strategies for pregnancy-associated TTP, particularly the role of targeted therapies, such as caplacizumab. Heightened clinical vigilance and timely intervention are crucial for improving prognosis in such complex cases.